2018
DOI: 10.1002/smll.201704296
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Mn3O4 Micro/Nanocuboids with In Situ Coated Carbon as Advanced Anode Material for Lithium‐Ion Batteries

Abstract: The electrochemical performance of most transition metal oxides based on the conversion mechanism is greatly restricted by inferior cycling stability, rate capability, high overpotential induced by the serious irreversible reactions, low electrical conductivity, and poor ion diffusivity. To mitigate these problems, highly porous Mn O micro/nanocuboids with in situ formed carbon matrix (denoted as Mn O @C micro/nanocuboids) are designed and synthesized via a one-pot hydrothermal method, in which glucose plays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 54 publications
4
70
0
Order By: Relevance
“…Fe 7 S 8 /N-C nanohybrids were prepared for FeMOF and FeMOF-S and analyzed by FTIR (Jin et al, 2019 ). In addition, energy dispersive spectroscopy (EDS) (Paolella et al, 2011 ; Ding et al, 2016 ; Guo et al, 2016 ), dynamic light scattering (DLS) (He et al, 2013 ; Ding et al, 2016 ), Raman spectroscopy (Gan et al, 2016 ; Guo et al, 2016 ), selected area electron diffraction (SAED) (Kar and Chaudhuri, 2004 ), X-ray absorption fine structure (XAFS) (Feng et al, 2013 ), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) (Jin et al, 2019 ), nitrogen adsorption–desorption isotherms and pore size distribution (Guo et al, 2016 ) analysis of iron sulfide have been reported as characterization systems.…”
Section: Synthesis Of Nano-sized Iron Sulfidesmentioning
confidence: 99%
“…Fe 7 S 8 /N-C nanohybrids were prepared for FeMOF and FeMOF-S and analyzed by FTIR (Jin et al, 2019 ). In addition, energy dispersive spectroscopy (EDS) (Paolella et al, 2011 ; Ding et al, 2016 ; Guo et al, 2016 ), dynamic light scattering (DLS) (He et al, 2013 ; Ding et al, 2016 ), Raman spectroscopy (Gan et al, 2016 ; Guo et al, 2016 ), selected area electron diffraction (SAED) (Kar and Chaudhuri, 2004 ), X-ray absorption fine structure (XAFS) (Feng et al, 2013 ), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) (Jin et al, 2019 ), nitrogen adsorption–desorption isotherms and pore size distribution (Guo et al, 2016 ) analysis of iron sulfide have been reported as characterization systems.…”
Section: Synthesis Of Nano-sized Iron Sulfidesmentioning
confidence: 99%
“…To overcome the above problems of MnO x (as well as other TMOs), many solutions have been attempted and can be majorly classified into two strategies: nanostructuring and carbon‐compositing . The former, by developing diverse nanostructures such as nanoparticles, nanosheets, nanocages, nanofibers, nanocubes, etc., brings in numerous benefits such as shortened ion diffusion path, enlarged electrochemically active surface, promoted electrolyte infiltration, as well as relieved lattice stress . The latter, by hybridizing with various kinds of carbonaceous materials including graphene, carbon nanotubes, carbon nanofibers, and amorphous carbon, etc., enables to greatly enhance electronic conductivity, buffer the cyclic volume fluctuation, and reinforce the electrode stability by providing structural supports for the active materials …”
Section: Introductionmentioning
confidence: 99%
“…Many transition metal oxides [7,8,9,10] show potential as promising anode candidates for LIBs by reason of their better theoretical capacity, high power density, and easy accessibility [11,12]. Among these materials, Co 3 O 4 is a potential anti-ferromagnetic p-type semiconductor with a spinel crystal structure, which can coordinate with eight lithium ions per single lattice and deliver a higher theoretical capacity of 890 mAh·g −1 [13,14].…”
Section: Introductionmentioning
confidence: 99%